A review on chemical and physical modifications of phytosterols and their influence on bioavailability and safety. Issue 20 (13th November 2022) - Feng, Simin; Wang, Liling; Shao, Ping; Sun, Peilong; Yang, Chung S.
Abstract: Phytosterols have been shown to lower cholesterol levels and to have antioxidant, anti-inflammatory and other biological activities. However, the high melting point and poor solubility limit their bioavailability and practical application. It is advantageous to modify phytosterols chemically and physically. This article reviews and discusses the chemical and physical modifications of phytosterols, as well as their effects on the bioavailability and possible toxicity in vivo. The current research on chemical modifications is mainly focused on esterification to increase the oil solubility and water solubility. For physical modifications (mainly microencapsulation), there are biopolymer-based, surfactant-based and lipid-based nanocarriers. Both chemical and physical modifications of phytosterols can effectively increase the absorption and bioavailability. The safety of modified phytosterols is also an important issue. Phytosterol esters are generally considered to be safe. However, phytosterol oxides, which may be produced during the synthesis of phytosterol esters, have shown toxicity in animal models. The toxicity of nanocarriers also needs further studies.